2004
DOI: 10.1097/01.wcb.0000098606.42140.02
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Astrocytic Energy Metabolism Depressant on 14C-Acetate Uptake in Intact Rat Brain

Abstract: Summary: Fluorocitrate, a selective astrocytic toxin, was microinjected into the right striatum of rat brain, and the regional distribution of 14 C-acetate was measured using autoradiography. A significant reduction (more than 80%) in 14 C-acetate uptake over a 5-minute period was observed in the right striatum, compared with that in the left striatum (saline infused), 4 hours after fluorocitrate (1 nmol/L) infusion. This effect was transient, and 14 C-acetate uptake had almost returned to normal at 24 hours a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 15 publications
1
33
0
Order By: Relevance
“…It was previously suggested that the astrocytespecific substrate acetate allows to measure metabolism in human brains in vivo (Hosoi et al, 2004;Muir et al, 1986). However, to our knowledge this is the first study using label clearance from brain after 1-11 C-acetate administration for the investigation of astrocytic oxidative metabolism in vivo.…”
Section: Discussionmentioning
confidence: 92%
“…It was previously suggested that the astrocytespecific substrate acetate allows to measure metabolism in human brains in vivo (Hosoi et al, 2004;Muir et al, 1986). However, to our knowledge this is the first study using label clearance from brain after 1-11 C-acetate administration for the investigation of astrocytic oxidative metabolism in vivo.…”
Section: Discussionmentioning
confidence: 92%
“…The response frequencies to a range of von Frey filament forces were determined, a stimulus-response frequency relationship established, and EF 50 values derived. After establishing the behavioral hyperalgesia at 1 d after CFA injection, fluorocitrate, a gliotoxin that is relatively selective against astroglia (Hosoi et al, 2004), was microinjected into the ventral Vi/Vc transition zone through a chronically implanted guide cannula (Fig. 8a).…”
Section: Glial and Il-1 Receptor Antagonist Inhibits Behavioral Hypermentioning
confidence: 99%
“…Fluorocitric acid inhibits aconitase, a TCA cycle enzyme, enriched in astrocytes, that transforms citrate into isocitrate (Peters, 1957). Thus, FC application results in interruption of ATP production and damage to astrocytes (Paulsen, et al, 1987;Hosoi, et al, 2004;Peters, 1957). On the other hand, glutamate reuptake via glutamate transporters and the cystine-glutamate antiporter is heavily dependent on astrocytes (Anderson and Swanson, 2000).…”
Section: Introductionmentioning
confidence: 99%